MEDIA EDUKASI TENTANG PENGENALAN DINI POSTPARTUM BLUES PADA IBU NIFAS DI RSUD DR DRADJAT PRAWIRANEGARA SERANG BANTEN - Umalihayati Umalihayati; Qonita Qonita (Gapenas Publisher, 2023)
Postpartum Blues can be experienced by every woman who has just given birth. The worldwide incidence rate is quite high, around 26-85% of postpartum women experience Postpartum Blues. For Indonesia, it is around 50-70%, and 24.7% in Dr.Dradjat Prwairanegara Hospital who experience Postpartum Blues. This happens because the mother is not ready to have a baby and is not fully ready to become a mother. Postpartum Blues if left unchecked and without a solution, can have a serious impact on postpartum depression. The target of this activity is all postpartum mothers who are treated at Dr.Dradjat Prawiranegara Hospital. The purpose of this activity is to provide knowledge about the introduction of Postpartum Blues. The method of implementation through the stages of preparation, implementation of health counseling and assessment. Outcome achievements in the form of a pocket book on Postpartum Blues and journal publications